Breaking cocoa pods, Trinidad, B.W.I. - (:unkn) unknown (Millards "The Cash Store" Trinidad, 2010)
A picture of a group of labourers sitting around a large pile of cocoa pods that was brought in from the fields by donkeys.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cocoa--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Working class--Trinidad and Tobago; Cocoa trade--Trinidad and Tobago; Draft animals--Trinidad and Tobago; Donkeys--Trinidad and Tobago; Cocoa processing--Trinidad and Tobago; East Indians--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago